(untitled) (Medical Forum Monthly, 2024)
Objective: This study assessed the knowledge, practice of standard hand hygiene in nursing staff to identify the causes of not adapting hand hygiene techniques during routine patient care. Study Design: A cross sectional study. Place and Duration of Study: This study was carried out in Karachi in various public sector hospitals i.e. Jinnah Postgraduate & Medical Centre, National Institute of Child Health, Civil Hospital Karachi, Sindh Institute of Urology Transplantation, National Institute of Cardiovascular Diseases. The study completed in six months from May to November 2010. Materials and Methods: A sample of 335 nursing staff was selected, convenient sampling was used, consent was taken. They were asked about their practices of hand hygiene through structured questionnaire at five major public sector hospitals of Karachi. Pakistan. Results: Out of 335 nursing personnel, 71.9% were unaware that washing hands under running water for 30sec to 1min remove most of the germs. 74.62% knows that hand washing is necessary. Regarding practices, 35.5% use sanitizers while 47.2% use antiseptic, normal soap for washing hands. 67.1% practice hand washing before & after coming in contact with patients. 43.7% took some treatment after needle prick while others (56.3%) didn’t feel the necessity to take any treatment, regardless of the risk of Hepatitis, HIV. 36.1% adopted sterile techniques after hand washing. Surveillance was below average (46.6%).. Conclusion: Hand hygiene knowledge, practices of nursing staff is part & parcel for minimizing infections. Adequate hand washing facilities, positive attitude towards hand hygiene, adherence to practice, strict surveillance system for hand hygiene is essential to combat increasing incidence of infections.